The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s13762-014-0655-3
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing a decentralized stormwater treatment system for an urbanized city with improper stormwater drainage facilities

Abstract: Urbanization involving replacement of previous areas with impervious surfaces and drainage channel modifications results in increased runoff volume leading to flooding and also in deteriorating the quality of the stormwater runoff. An effective and efficient stormwater management is needed in the urban areas for mitigating the impacts and overcoming the problems associated with the urban stormwater. An attempt has been made in the present study to investigate the relationships between stormwater quality and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Both natural and human activities cause air pollution in rural areas (Dey et al 2004 ). Natural sources of air pollution occur when pollutants are generated from various natural sources (i.e., animals, plants, land resources, forest fires, coal fires, dust storms, volcanic eruptions, and sand storms) and are dispersed in the atmosphere naturally (Arora and Reddy 2013 , 2014 , 2015 ; Li et al 2010 ). Solid fuel combustion (cooking and heating) as well as agriculture activities, mining (opencast and underground) activities, industrial activities (cement production and coal processing), all contribute significant air pollutants into the ambient atmosphere (Xia et al 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both natural and human activities cause air pollution in rural areas (Dey et al 2004 ). Natural sources of air pollution occur when pollutants are generated from various natural sources (i.e., animals, plants, land resources, forest fires, coal fires, dust storms, volcanic eruptions, and sand storms) and are dispersed in the atmosphere naturally (Arora and Reddy 2013 , 2014 , 2015 ; Li et al 2010 ). Solid fuel combustion (cooking and heating) as well as agriculture activities, mining (opencast and underground) activities, industrial activities (cement production and coal processing), all contribute significant air pollutants into the ambient atmosphere (Xia et al 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Good quality of treated stormwater (taking only the analysed ratios into account) also makes it possible to use it for household purposes. Other authors have demonstrated that integrated management of stormwater can generate considerable economic benefits (savings on tap water), hydrological benefits (flood protection) and ecological benefits (protection of habitats) (Mitchell et al 2007 ; Sharma et al 2008 ; Yu et al 2013 ; Tao et al 2014 ; Arora and Reddy 2015 ; Pennino et al 2016 ). In the conditions of the study, water from the retention pond can be used, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The geological environment, recovery, and anthropogenic activities like domestic, industrial, commercial, mining, and cultivation, directly affect the regional quality of water (Singh et al., 2004; Zhou et al., 2020). In addition to these sources, storm water is also considered a significant contributor of pollutants to surface and groundwater (Arora & Reddy, 2013; Arora & Reddy, 2014, 2015). Contamination of surface and groundwater by these activities is a serious problem, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%